Se da E(x) = (x+1)^2 + (x-1)^2 - (x-2)(x+2). Calculati E(1) + E(√2)
moisescuraluca:
Ce e „^ ”??
Răspunsuri la întrebare
Răspuns de
1
..........................
Anexe:
Răspuns de
2
E(x)=(x+1)²+(x-1)²-(x-2)(x+2)
E(1) E(√2)
(x+1)²+(x-1)²-(x-2)(x+2)=x²+2x+1+x²-2x+1-x²-2x+2x+4=x²+6
E(1)=1²+6=7
E(√2)=(√2)²+6=2+6=8
E(1) E(√2)
(x+1)²+(x-1)²-(x-2)(x+2)=x²+2x+1+x²-2x+1-x²-2x+2x+4=x²+6
E(1)=1²+6=7
E(√2)=(√2)²+6=2+6=8
Alte întrebări interesante
Engleza,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
10 ani în urmă
Matematică,
10 ani în urmă